Development of electrochemical immunosensors for HER-1 and HER-2 analysis in serum for breast cancer patients - Wignarajah, Shayalini; Chianella, Iva; Tothill, Ibtisam E. (MDPI, 2023)
In this work, two human epidermal growth factor receptors, HER-1 and HER-2, were selected as biomarkers to enable the detection of breast cancer. Therefore, two biosensors were developed using gold sensor chips coupled with amperometric detection of the enzyme label horse radish peroxidase (HRP). The biosensors/immunosensors relied on indirect sandwich enzyme-linked immunosorbent assays with monoclonal antibodies (Ab) against HER-1 and HER-2 attached to the sensors to capture the biomarkers. Detection polyclonal antibodies followed by secondary anti-rabbit (for HER-1) and anti-goat (for HER-2) IgG antibody-HRP were then applied for signal generation. In buffer, the developed sensors showed limits of detections (LOD) of 1.06 ng mL−1 and 0.95 ng mL−1 and limits of quantification (LOQ) of 2.1 ng mL−1 and 1.5 ng mL−1 for HER-1 and HER-2, respectively. In 100% (undiluted) serum, LODs of 1.2 ng mL−1 and 1.47 ng mL−1 and LOQs of 1.5 ng mL−1 and 2.1 ng mL−1 were obtained for HER-1 and HER-2, respectively. Such limits of detections are within the serum clinical range for the two biomarkers. Furthermore, gold nanoparticles (AuNP) labelled with secondary anti-rabbit and anti-goat IgG antibody-HRP were then used to enhance the assay signal and increase the sensitivity. In buffers, LODs of 30 pg mL−1 were seen for both sensors and LOQs of 98 pg mL−1 and 35 pg mL−1 were recorded for HER-1 and HER-2, respectively. For HER-2 the AuNPs biosensor was also tested in 100% serum obtaining a LOD of 50 pg mL−1 and a LOQ of 80 pg mL−1. The HER-2 AuNP electrochemical immunosensor showed high specificity with very low cross-reactivity to HER-1. These findings demonstrate that the two developed sensors can enable early detection as well as monitoring of disease progression with a beneficial impact on patient survival and clinical outcomes.
Keywords: electrochemical immunosensor; HER-1 or EGFR; HER-2; serum; amperometry; gold sensor chips; breast cancer; gold nanoparticle